Práticas discursivas e governamentalidade: uma análise da implementação do programa nacional de formação de professores da educação básica na Universidade Federal do Maranhão - MARINHO, Raimunda Ramos (2024)
The purpose of this thesis is to analyze the process of implementing the National Basic Education Teacher Training Program at UFMA and the discursive practices in dimensional contexts under the influence of neoliberal discourse in education. The research is part of the History and Educational Policy research line of the Postgraduate Program in Education at the Federal University of Maranhão (UFMA), as part of the doctoral requirement. The general objective is to analyze the movement of governmentality in the implementation of the PARFOR Program at UFMA, as suggested by the discursive practices in the contexts of Public Policy through the participation of Mid-Level Managers. The theoretical-methodological approach adopted is based on Michel Foucault's theoretical-analytical tools: power knowledge and biopolitical governmentality, with the aim of understanding discursive practices in the dimensional contexts of politics in the light of Michel Foucault, and Stephen J. Ball's Policy Cycle Approach, based on Discourse Analysis. The empirical corpus was gathered by means of documentary and bibliographical research and narrative interviews with participants in the PARFOR program, the aim of which, it should be emphasized, is to do research with, not on, Middle Managers. The theoretical framework is based on authors such as Abrucio (1997, 2000); Afonso (1999, 2001); Arretche,1999; Azevedo, 2004; Ball, Maguire, Braun, 2021; Ball and Mainardes,2024; Barroso, 2006; Dardot and Laval, 2016; Dye Barroso, 2006; Dardot and Laval, 2016; Dye, 2010; Frey, 2000; Foucault 2008, 2014; Gadelha, 2009; Melo, 1999; Milani, 2008; Veiga-Neto, 2013, 2017; Weber, 1974. It was evident that the governmentality of the PARFOR Program is based on universal devices, which manifest themselves as normative power and regulatory power, programmed to normalize the management of the policy. On the other hand, in this context of supposed political decentralization that is not legitimized through legal and normative appeals, power is dissipated institutionally, which allows some GMEs a certain degree of autonomy, hierarchically, in the process of recontextualizing the policy. In this study, we examined relevant points that demonstrate proactive management initiatives, the results of which highlight the leadership and proximity of the ruler located at central level in the profile of this subject, giving them, in proportion, greater or lesser accessibility to power. We conclude that, although the research examined relevant points that demonstrate proactive management initiatives, it is a governance model based on methods of internal control and accountability, which makes it difficult for GMEs to exercise participation and autonomy, and inhibits the development of a manager profile with creative engagement. At the institutional level, it became clear that the rules exercise biopolitical control over the technical and operational functioning of the PARFOR Program at UFMA. In . In this way, there is a subjectivization of the subjects, such as the little political participation of the frontline managers in the various relationships experienced by these individuals, at the bottom, far from the state spheres and with the bureaucratic overload focused on meeting targets, which curbs the creative engagement of the GMEs in the management of the Program.